REGULASI, ANGGARAN, DAN PROGRAM DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA SEMARANG DALAM PENGEMBANGAN INDUSTRI JAMU - Desy Rachmanita Pratiwi; Kushandajani .; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2016)
This research is based on utilization of nutritious plant diversity by people to be used as Indonesian traditional herbal medicine called Jamu. Along with development of technology, industry of herbal medicine start to popping up, but not as fast as development of chemical medicine and foreign herbal medicine. However, developing of herbal medicine becoming moved down and hence government intervening is needed. The problem of this research is the role office of industry and commerce in advacing traditional herbal medicine industry at Semarang in regulation, budgets and program during 2014.The goal of the research is explaining role of the office of industry and commerce in advacing traditional herbal medicine industry at Semarang whitin aspects such as regulation, budgets and program. This research using qualitative-descriptive method with the type of data used are primary and secondary data through interviews and collectif document.The result shows that in advacing traditional herbal medicine industry at Semarang, office of industry and commerce at Semarang in aspect regulation making an industy cluster which is focusing on small and medium industry to joined in a clusters of herbal medicine in Semarang. In budget aspect, to advacing herbs medicine industry cluster has a limited budget. Its because they must share it with another clusters. In program aspect, there are some program such as taking and drinking herbs medicine movement, using land area for medication planting utilization, socialization to take herbal medicine movement. The programs are good, but has not been efficient due to small budget and murky regulation.Researcher suggess to review aspects of the regulation, budget and program in advacing traditional herbal medicine industry at Semarang in order to optimizing and advancing that herbal medicine industry in Semarang.Keywords: office of industry and commerce Semarang, herbal medicine, regulation, budget, program.